2021
DOI: 10.1097/rlu.0000000000003655
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Membrane Antigen Expression in Patients With Differentiated Thyroid Cancer With Thyroglobulin Elevation and Negative Iodine Scintigraphy Using 68Ga-PSMA-HBED-CC PET/CT

Abstract: Purpose of the Report Prostate-specific membrane antigen (PSMA) is a member of superfamily of zinc-dependent exopeptidases that is robustly expressed in prostate cancer cells and nonprostatic solid tumor neovasculature including microvessels of thyroid tumors. Its expression in differentiated thyroid cancer (DTC) has been confirmed in many recent studies, but systematic studies exploring PSMA expression in patients with DTC with thyroglobulin elevation and negative iodine scintigraphy (TENIS) are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Six full-text papers assessing the potential role of PSMA radioligands in the diagnostics and therapy of differentiated thyroid cancer (DTC) were reviewed [ 40 , 41 , 42 , 43 , 44 , 45 ]. Out of the six included studies, four had a prospective design [ 40 , 42 , 43 , 45 ]. The sample size varied from 2 to 11 and from 3 to 43 for patient and lesion analyses, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six full-text papers assessing the potential role of PSMA radioligands in the diagnostics and therapy of differentiated thyroid cancer (DTC) were reviewed [ 40 , 41 , 42 , 43 , 44 , 45 ]. Out of the six included studies, four had a prospective design [ 40 , 42 , 43 , 45 ]. The sample size varied from 2 to 11 and from 3 to 43 for patient and lesion analyses, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In all studies but one [ 40 , 41 , 42 , 43 , 44 ], PET/CT was performed using 68 Ga-PSMA-11, whereas the remaining study used 18 F-DCFPyl [ 45 ]. In one study, in addition to 68 Ga-PSMA-11 PET/CT as diagnostic compound, 177 Lu-PSMA-617 RLT therapy was performed in two out of five patients [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in another series comprising nine patients with TENIS syndrome, the authors reported PSMA-positive disease in only 5/9 (56%) patients compared to FDG-positive disease in 8/9 (89%) patients. Further, out of a total of 14 lesions, [ 68 Ga]Ga-PSMA-11-PET/CT detected less lesions compared to 2-[ 18 F]FDG-PET/CT (9/14 versus 11/14, respectively) ( 23 ). Given the lower detection rates, the role of [ 68 Ga]Ga-PSMA-11-PET/CT in RAIR-DTC lies primarily in patient selection for [ 177 Lu]Lu-PSMA-617 therapy, and not for diagnostic purposes.…”
Section: Theranostics In Rair-dtcmentioning
confidence: 99%
“…Metastatic lesions in RAI-refractory DTC patients were demonstrated by PET/CT using 68 Ga-based PSMA, which found additional metastatic lesions compared with [ 18 F]FDG [ 60 , 61 , 62 ]. Vries et al treated two RAI-refractory DTC patients with [ 177 Lu]Lu-PSMA-617.…”
Section: Non-iodine-related Pet Radiopharmaceuticalsmentioning
confidence: 99%